The role of protein kinase CK2 in skeletal muscle: Myogenesis, neuromuscular junctions, and rhabdomyosarcoma - Hashemolhosseini, Said (Neuroscience Letters, 2020)
For the first time, a review article focuses exclusively on the role of the protein kinase CK2 in mono- and poly-nucleated mammalian skeletal muscle cells. While CK2, a pleiotropic serine/threonine kinase was originally thought to phosphorylate mainly casein, later evidence found glycogen phosphorylase and glycogen synthase also to be a target, linking the enzyme to muscle biology. Indeed, recent studies have shown that CK2 is involved in many different steps in the biology of striated skeletal muscle, such as myogenesis and homeostasis in the adult muscle, and even at the neuromuscular junctions, the points of contact between the muscle fibers and the motor nerves end. Next to the role of CK2 in muscle physiology, this review also highlights the contribution of CK2 in muscle pathologies, such as muscle tumors and myopathies.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Myogenesis; Neuromuscular junction; Protein kinase CK2; Rhabdomyosarcoma; Skeletal muscle